2021
DOI: 10.1186/s13195-021-00816-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics and exploratory pro-cognitive effects of HTL0018318, a selective M1 receptor agonist, in healthy younger adult and elderly subjects: a multiple ascending dose study

Abstract: Background The cholinergic system and M1 receptor remain an important target for symptomatic treatment of cognitive dysfunction. The selective M1 receptor partial agonist HTL0018318 is under development for the symptomatic treatment of Dementia’s including Alzheimer’s disease (AD) and dementia with Lewy bodies (DLB). We investigated the safety, tolerability, pharmacokinetics and exploratory pharmacodynamics of multiple doses of HTL0018318 in healthy younger adults and elderly subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
4
11
0
Order By: Relevance
“…The pharmacokinetics of HTL0018318 were well-characterized in plasma and urine. The characteristics were comparable to the pharmacokinetic data observed in previous studies [ 12 , 14 ]. Median t max (1.74–2.5 h) and mean half-life following the fifth dose (10.5–13.7 h) did not appear to change with respect to HTL0018318 dose level and co-dosing with donepezil.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The pharmacokinetics of HTL0018318 were well-characterized in plasma and urine. The characteristics were comparable to the pharmacokinetic data observed in previous studies [ 12 , 14 ]. Median t max (1.74–2.5 h) and mean half-life following the fifth dose (10.5–13.7 h) did not appear to change with respect to HTL0018318 dose level and co-dosing with donepezil.…”
Section: Discussionsupporting
confidence: 88%
“…The side effect profile observed in this study was comparable to that observed in the single ascending dose (SAD) and multiple ascending dose (MAD) studies with HTL0018318 [ 12 , 14 ]. Only nausea and vomiting were reported more frequently than in the SAD and MAD study.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations